Evaluation of β-hCG regression after evacuation of molar pregnancy as a predictive factor for malignant GTN - Kader, Mousumi; Elora, Ashfi Laila; Chowdhury, Mina; Afrose, Taslima; Amin, Rogina; Sultana Jolly, Rabeya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Gestational trophoblastic disease (GTD) is a group of disorders identified by abnormal proliferation of trophoblastic tissue. The general term GTN is used to describe a wide range of trophoblastic diseases including invasive mole, choriocarcinoma, epithelioid trophoblastic tumor, and placental site trophoblastic tumor. The persistence of GTN post-molar pregnancy can be efficiently detected with serial measures of the β subunit of hCG, or β-hCG. Therefore, this study aimed to evaluate the β-hCG regression after evacuation of molar pregnancy as a predictive factor for malignant GTN. Methods: This was a prospective analytical study conducted in the Gynaecological Oncology Unit and Department of Obstetrics and Gynecology, Dhaka Medical College Hospital, Dhaka, Bangladesh during the period from January 2022 to December 2022. In our study, we included 50 patients with molar pregnancies attending the Gynaecological Oncology Unit and Department of Obstetrics & Gynecology of DMCH. Result: The mean age of participants was 23.5 years. The GTN was diagnosed among 24% of patients. In 2nd week, the mean β-hCG was found 91027.50±24430.53 miU/ml in the persistent GTN group and 19339.68±13978.59 miU/ml in the remission group. The mean Β-hCG significantly decreased to 64399.33±23404.81 and 4.47±2.57miU/ml in the persistent GTN and remission group respectively in the 15th week (p<0.05). Conclusion: This study found that serum β-hCG levels in the 2nd, 3rd, and 4th weeks following molar evacuation can predict over 24% of patients who developed GTN after molar evacuation. The decline in serum β-hCG levels during weeks was statistically linked to the development of GTN.